Influence of lateral preference and structural inequalities on asymmetries of upright posture in swimmers - DOI: 10.4025/reveducfis.v20i3.7316 - Mann, Luana (2009)
The aim of this study was to verify if athletes involved with tasks of rhythmic movements of the lower limbs (MI) can present standing asymmetries due to lower limbs structural inequalities (DMI) influenced by leg preference. We evaluated 18 swimmers of both genders. Leg length was measured and subjects were assigned in groups: group 1 with DMI equal or lesser than 0.4 cm, group 2 withDMI ranging from 0.5 to 0.9 cm, and group 3 with DMI equal or higher than 1.0 cm; leg preference was assessed by kicking leg. Stabilometry was employed to the assessment of vertical ground reaction force (Fz) while standing. There was no effect of DMI on the Fz, no effect of leg preference on Fz, or significant interactions between them. Discrete structural differences and leg preference did not determine asymmetry in the vertical force during standing in swimming athlete.